The Experience of Nursing Students in the Clinical Learning Using Peer Learning Method - Hamzah, Nuhla Nuhbah; Putri, Suci Tuty; Sumartini, Sri (Jurusan Keperawatan FIKES UNSOED, 2019)
Clinical learning greatly determines the quality of graduates in nursing education. In the clinical learning process students tend to be reluctant and afraid to ask questions and express opinions to lecturers and advisors, but students will be more courageous to ask and express opinions about the courses to other students. Peer learning is a learning strategy where students who have high absorption to become tutors for their friends who have not understood the material for a particular purpose and this method can be an alternative in clinical learning. The study aims to explore students experience on clinical nursing education with peer learning method. The research method which is utilized to develop the study was the qualitative method with phenomenology approach.Ã‚Â The 8 participants in the research students collage base goal of research have been administered. The data analysis of taking interview from participant use Thematic Content Analysis. The data analysis reported that The Learning Experience, Self-Esteem, Leadership and Development of clinical skills.Ã‚Â Peer learning can make students' knowledge grow, more independent, more initiative, more courageous, able to train leadership and improve clinical skills. To sum up, the development of strategy peer learning are able to enhance the skills of nursing students.